PENGEMBANGAN LKPD BERBASIS PENDEKATAN ETNOMATEMATIKA PADA MATERI PENYAJIAN DATA - Erni Hastuti; Ahmad Fauzan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to design a valid and practical based on an ethnomathematical approach to assist teachers in presenting data presentation materials. It was expected that the LKPD would facilitate students to understand the materials since they came from the culture them. This study utilized the Plomp development model. The development stages of LKPD were conducted until one-to-one and small group trials at grade V of SDN 01 and SDN 05 Koto Baru Dharmasraya. This study revealed that 1) the validity was 3.63 with a very valid category, 2) the practicality result from the students was 93.05 with a very practical category, and 3) the practicality results from the teachers was 100 with a very practical category. Based on the results, this study concluded that the LKPD based on the ethnomathematical approach for data presentation material was very valid and practical. Thus, teachers could use this LKPD in the learning process at elementary schools, especially at grade V.